Contextual, structural, and mental health experiences of children of women engaged in high-risk sexual behaviour in Kampala: a mixed method study - Agnes Ssali; Agnes Ssali; Georgina Nabaggala; Michael C. Mubiru; Ibrahim Semakula; Janet Seeley; Janet Seeley; Rachel King; Rachel King (Frontiers Media S.A., 2023)
Children born to women who sell sex for money or commodities may face economic and social insecurity because of their mother's work, particularly in settings where sex work is illegal. From October 2020 to May 2021, we conducted a study with 60 children aged 12-24 years, born to sex workers in Kampala, Uganda. The children took part in 60 semi-structured interviews, 20 life history interviews, and 4 focus group discussions, which were used to explore their social, economic, and mental health experiences and investigate their vulnerabilities and resilience. Quantitative data were collected using REDcap, and descriptive analysis was done using Stata 14. Qualitative data were collected using semi-structured topic guides, and data analysed thematically. We explored findings in relation to a wellbeing framework. The findings showed that children experienced contextual and structural hardships, including incomplete and irregular schooling, a lack of privacy at home, food insecurity, and physical and psychological violence from relatives and sometimes from their mothers. Some children reported mental wellbeing struggles with hopelessness, nervousness, and sadness. Alcohol and drug use were common in most families. Community social network support systems, including neighbours and grandparents, were important; most children had absentee fathers. Some children suspected or knew how their mother earned her income. Resilience for most children was tagged to support from close networks and financial support from the government and civil society. Children of sex workers in Kampala experience structural, contextual, and mental health challenges but have a positive attitude towards the future. It is important to strengthen community support systems for these children and those living in similar circumstances in low- and middle-income countries.